The sting [videorecording (DVD)] / by David S. Ward, a Zanuck/Brown presentation ; produced by Tony Bill and Michael and Julia Phillips ; written by David S. Ward ; directed by George Roy Hill. - Ward, David S., 1945-; Redford, Robert; Newman, Paul, 1925-2008; Shaw, Robert, 1927-1978; Durning, Charles, 1923-2012; Brennan, Eileen; Hamlisch, Marvin (Legacy series., 2005)
Robert Redford and Paul Newman star as two con men in the 1930s, out to avenge the death of a mutual friend. They seek revenge on crime lord Robert Shaw with a 'sting' that is one of the greatest double-crosses in movie history.